LBA12Updated results of activity of durvalumab in advanced endometrial cancer (AEC) according to mismatch repair (MMR) status: The phase II PHAEDRA trial (ANZGOG1601). (24th November 2019) - Antill, Y; Kok, P S; Stockler, M R; Robledo, K; Yip, S; Parry, M; Smith, D; Spurdle, A; Barnes, E; Friedlander, M L; Baron-Hay, S; Shannon, C; et al.
Abstract: Background: Durvalumab monotherapy has demonstrated promising objective tumour response (OTR) and safety in advanced endometrial cancer with deficient MMR. We report here updated OTR, progression-free survival (PFS) and overall survival (OS) results based on central pathology MMR review from the PHAEDRA trial. Methods: Participants (pts) had MMR-proficient (pMMR) or -deficient (dMMR) AEC progressing after 0-3 lines of chemotherapy and were treated with durvalumab 1500mg IV Q4W. The primary endpoint was OTR (complete response [CR] or partial response [PR] by iRECIST). Secondary endpoints included PFS, OS, OTR by RECIST 1.1, adverse events, quality of life, and tertiary translational objectives to determine associations between molecular biomarkers and OTR. Results: 71 pts with AEC were recruited from Feb 2017 to Sep 2018: 36 dMMR and 35 pMMR based on central MMR review. Median follow-up for OS were 16 vs 21 months in dMMR vs pMMR pts. Median age: 67 (range 36-81); ECOG PS: 0-1 in 96%, and 2 in 4%. Pathology: endometrioid in 94% and 57%; serous in 0% and 31%; grade 3 (most recent histology): 41% and 85% (dMMR and pMMR respectively). Durvalumab was the 1st, 2nd and subsequent line of non-hormonal therapy in 58%, 39%, and 3% pts with dMMR and 9%, 63%, and 29% pts with pMMR. Among dMMR pts, the OTR rate was 47% (17/36, 95% CI 32-63%): 6 CR, 11 PR and 6 stable disease (SD). OTR rate was 57% as 1st line and 38% as 2nd line. Among pMMR pts, the OTR rate was 3% (1/35, 95% CI 1-15%): 1 PR and 10 SD. Median PFS was 5.5 vs 1.8 months in dMMR vs pMMR pts. 12-month OS was 71% vs 51% in dMMR vs pMMR, with median OS not reached for dMMR vs 11.5 months for pMMR participants. Conclusions: Durvalumab monotherapy showed promising activity and safety in AEC with dMMR regardless of prior lines of chemotherapy, but there was limited evidence of activity in AEC with pMMR. Clinical trial identification: ACTRN12617000106336. Legal entity responsible for the study: University of Sydney. Funding: AstraZeneca. Disclosure: Y. Antill: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Amgen. M.R. Stockler: Research grant / Funding (institution): As. D. Smith: Honoraria (self): Merck Sharp & Dohme; Shareholder / Stockholder / Stock options: SNP pathology. M.L. Friedlander: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Takeda. P.J. Beale: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Roche. T. Meniawy: Research grant / Funding (self): AstraZeneca.